PENGARUH PROFITABILITAS, CAPITAL INTENSITY RATIO, SIZE, LEVERAGE, KEPEMILIKAN INSTITUSIONAL, DAN KOMPENSASI DEWAN KOMISARIS SERTA DEWAN DIREKSI TERHADAP MANAJEMEN PAJAK ( Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2015 – 2017 ) - Natasha, Ayu; Raja, Satriawan Adri; Adhitya, Putra Agri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the influence of profitability, capital intensityratio, size, leverage, institutional ownership, and compensation of commissionerand director to tax management. Tax management is a dependent variable in thisstudy that measured by book tax differences (BTD). The population used in thisstudy is manufacture companies listed in Indonesia Stock Exchange period 2015-2017 which amounted to 163 companies. The sampling technique used purposivesampling technique for this study had a particular sample criteria are adapted to thepurpose of research . Based on purposive sampling method, the number of samples inthis study is 46 companies. But, researcher removed outlier from datasbase,untiltotal samples used is 35 companies. Data analyzed by classic asumption tests andexamine hypothesis by multiple regression method. These results indicate that the5% significance level, profitability, capital intensity ratio, size, and institutionalownership have a significant effect to tax management. While the other variable,leverage and compensation of commissioner and director do not have significanteffect to tax management.Keywords : Tax Management, Profitability, Capital Intensity Ratio, Size,Leverage, Institutional Ownership, and Compensation ofCommissioner and Directors.